2019
DOI: 10.3389/fimmu.2019.01428
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 1946 Cases of POEMS Syndrome in Chinese Subjects: A Literature-Based Study

Abstract: POEMS syndrome is a rare paraneoplastic disorder characterized secondary to a rare plasma cell dyscrasia. Here, we aimed to analyze the clinical characteristics of large sample cases of POEMS in Chinese subjects through making a review of the Chinese literature. Four databases were electronically searched from inception until October 2016. Case reports and case series were identified. Six hundred studies with 1946 participants were identified. The first case was reported in 1986, and the number of reported cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 61 publications
2
25
1
8
Order By: Relevance
“…Previous studies have reported median survival time after diagnosis of only 165 months and 30 months respectively for POEMS and MCD patients. 15 A recent study by Wang et al 16 reported that most patients died due to cardiorespiratory failure, capillary leakage complications, and infection during the disease course. The total number of presenting features during the initial diagnosis of the disease was insignificant in predicting patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported median survival time after diagnosis of only 165 months and 30 months respectively for POEMS and MCD patients. 15 A recent study by Wang et al 16 reported that most patients died due to cardiorespiratory failure, capillary leakage complications, and infection during the disease course. The total number of presenting features during the initial diagnosis of the disease was insignificant in predicting patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Аналогичные данные приводят китайские авторы. Так, по данным регистра Китайской Народной Республики, при пер вичной постановке диагноза периферическая нейро патия встречалась в 60,44 % случаев, отечный синд ром -в 15,72 %, эндокринопатии -в 9,87 %, кожные изменения -в 8,05 % и органомегалия -в 2,13 % [51].…”
Section: клиническая картинаunclassified
“…No circulating autoantibodies against hormones or hormone receptor nor characteristic histological findings have been identified. It has been hypothesized that the overexpression of VEFG could alter the local balance of angiogenic factor and, consequently, affect the regulation of (Marchand et al 2017;Wang et al 2019).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Prophylaxis with anti-aggregants is recommended for the high risk of thrombosis, in association with orthotics, physical therapy, and c-PAP in case of bone/muscle or lung involvement, respectively. No specific recommendations the management of endocrine disorders have been formulated (Dispenzieri 2019;Wang et al 2019).…”
Section: Treatment and Outcomementioning
confidence: 99%